Channel characterisation in rural railway environment at 28 GHz. Issue 8 (7th May 2019) - Wang, Longhe; Ai, Bo; He, Danping; Yi, Haofan; Zhong, Zhangdui; Kim, Junhyeong
Abstract : Nowadays, rail traffic is expected to evolve into a new era of 'smart rail mobility', where trains, infrastructure, travellers and goods will be increasingly interconnected. Railway communications are required to support various high‐data‐rate applications, the communication system should be carefully designed, which makes railway scenario becomes a more and more important communication scenario. In this study, the channel characteristics are analysed for rural railway at 28 GHz. Four different deployments are considered via calibrated ray‐tracing simulations in the target environment. The large‐scale parameters of the mmWave channel, including the path loss, root‐mean‐square delay spread, Rician K ‐factor, angular spreads and cross‐polarisation ratio are explored. The statistical properties, decorrelation distance and cross‐correlations are analysed as well. The studied channel characteristics can be used to support the link level and system level design of the communication system in the similar environment.